2020
DOI: 10.1016/j.diamond.2019.107563
|View full text |Cite
|
Sign up to set email alerts
|

On the adhesion and wear resistance of DLC films deposited on nitrile butadiene rubber: A Ti-C interlayer

Abstract: To promote the adhesion strength between diamond-like carbon (DLC) films and nitrile butadiene rubber (NBR) substrates, titanium-doped carbon (Ti-C) films prepared by dual-target magnetron sputtering under varied substrate bias voltages were used as an interlayer on the rough NBR. The surface topography and structure of Ti-C films were investigated by atomic force microscopy (AFM) and Raman spectra. Raman analysis indicates that the increase of substrate bias voltage leads to an increase of the number or the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There is a slight shift to the higher wavenumber as the incorporation of F in the film for the D peak position whereas the G peak positions are approximately the same for both films. The similar ID/IG ratios and G peak positions suggest that there is a similar amount of graphite clusters in both deposited films [26,27], which means that 4% F content does not impose a significant effect on the chemical structure of deposited thin films. The coefficients of friction (COFs) of uncoated NBR, PU rubber samples, DLC and F-DLC coated rubbers are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 81%
“…There is a slight shift to the higher wavenumber as the incorporation of F in the film for the D peak position whereas the G peak positions are approximately the same for both films. The similar ID/IG ratios and G peak positions suggest that there is a similar amount of graphite clusters in both deposited films [26,27], which means that 4% F content does not impose a significant effect on the chemical structure of deposited thin films. The coefficients of friction (COFs) of uncoated NBR, PU rubber samples, DLC and F-DLC coated rubbers are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 81%
“… 37 Moreover, as shown in Figure S5f (Supporting Information), the P 2p high-resolution XPS spectra of yeast cells can be deconvoluted into two peaks at 133.06 eV (P–O) and 134.07 eV (C–O–P), 38 , 39 which confirms the presence of −PO 3 on the surface of yeast cells. After the formation of yeast@ a MIL-125 (Ti) composites, it could be clearly observed that the peaks at 283.2, 528.94, 531.11, 400.35, 132.06, and 133.31 eV were attributed to C–Ti–O, 40 lattice oxygen (O 2– ), 34 Ti–OH, 33 , 41 N–C=O, 42 P–C, and P–O bonds, 38 respectively, suggesting no characteristic binding energy of Ti–N (456.4 eV) and Ti–P bonds (455.40 eV). 43 Notably, the binding energies and atomic proportions (atom %) of C 1s, O 1s, N 1s, and P 2p in −COOH, −OH, amide and −PO 3 groups have significantly changed after the formation of yeast@ a MIL-125 (Ti) composites ( Figure S5c–f , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…There are manifold options to reach improved coating stability in addition to mere graded a-C:H microstructures. Supporting interlayers-such as TiC, TiAlC, TiAlN, TiAlC, and SiN x interlayer-are state of the art or state of research [23][24][25][26] for several applications. The long-term effect of any interlayer in biomedical environment and other changes on the tribological system need to be verified.…”
Section: Discussionmentioning
confidence: 99%